Morphological Identification based on Lineament and Density Pulai Pinang Region and Surroundings Lahat District, Province South Sumatra - Hibatullah, Muhammad Ariq; Dyah Hastuti, Endang Wiwik; Idarwati, Idarwati (Journal of Geology Sriwijaya, 2024)
Morphological identification based on lineament and geological structure analysis has beencarried out in Pulau Pinang Village and its surroundings, Lahat Regency, South SumatraProvince. The initial stage in identification uses a remote sensing approach through lineamentanalysis using DEMNAS data. This research is focused on lineament analysis with DigitalElevation Model (DEM) data to identify geological and morphological structures in the studyarea. The methods used in the research are observative, analytic and interpretive. Theresearch was conducted with DEMNAS data which was then extracted using PCI Geomaticasoftware and after that it was correlated with geological structure data in the field. Lineamentanalysis used is the length, orientation and density of the lineament. This study aims tointerpret the relationship between lineament data and the results of field data. The researchlocation is controlled by the geological structure, namely fracture and morphology. Based onthis research, data obtained, the Pulau Pinang area is composed of fractures which areanalyzed to produce a right horizontal fault and 3 geomorphic units / landforms, namely theIrregular Meander Channel (CIM), Steep Slope High Hills (PTBC), Denudasional Hills (PD),and Low Hills (PR).